The economic burden of scrub typhus disease among the tribal ethnic groups (Mizo) of Mizoram State, Northeast India - Van Ramliana; Lalfakzuala Pautu; Gabriel Rosangkima; Rebecca Lalduhawmi; Hun Ropuia; Ralte Vanlalawmpuii; Mary Lalramchuani; Lal Ramliana (BMC Public Health)
Abstract Background Orientia tsutsugamushi is the pathogen of scrub typhus, a rickettsial infection that poses a serious threat to many countries including India where the disease case-fatality was as high as 6%. The present study was aimed at determining the prevalence of scrub typhus disease and estimating the economic impact of the disease among the Mizo tribe of Mizoram State, Northeast India. Materials & Methods The present study was a three-year retrospective, cross-sectional study conducted in 10 selected PHCs of Mizoram. The line-listing data of three years (2021—2023) on scrub typhus was used for the epidemiological investigation. The minimum economic burden of scrub typhus was evaluated using data collected by personal interviews with the scrub typhus survivors among the Mizo tribe. Results A total of 22870 scrub typhus cases were recorded among the tribal ethnic groups (Mizo) in Mizoram State in the year 2021—2023, with an annual incidence of 571.48 per 100,000 persons. A positive relationship between age and disease incidence was observed, with a higher burden (1964.5 per 100,000 persons) among the elderly population (70 + years). The disease incidence rate also showed increasing trend and seasonality, with the peak of cases during August-October. The overall three years economic burden was found to be US$ 730,003.80, with an average annual economic burden of US$ 243,334.60 contributing 0.08% of the gross state domestic product (GSDP). An increasing trend in scrub typhus economic burden was observed during the study period. Conclusions According to the current study, Mizoram State's tribal ethnic groups have a remarkably high incidence rate of scrub typhus disease causing a significant financial impact. Therefore, prevention and control measures for the disease are unavoidable.